Age-related differences in the characteristics of persistent postural-perceptual dizziness - Fukushima, Akina; Kabaya, Kayoko; Minakata, Toshiya; Katsumi, Sachiyo; Esaki, Shinichi; Iwasaki, Shinichi (Frontiers in Neurology, 2024)
Objective: To investigate differences in the clinical characteristics of patients with persistent postural-perceptual dizziness (PPPD) according to age. Methods: We retrospectively reviewed 143 patients diagnosed with PPPD. Patients were classified into three groups by age: young group (19 to 44 years, n = 60), middle-age group (45 to 64 years, n = 56), old group (65 to 85 years, n = 27). Demographic data, scores of the Dizziness Handicap Inventory (DHI), the Niigata PPPD Questionnaire (NPQ), the Hospital Anxiety and Depression Scale (HADS), precipitating conditions, and the results of vestibular function tests including caloric testing, video head impulse test (vHIT), cervical and ocular vestibular evoked myogenic potentials (cVEMPs and oVEMPs), and posturography, were compared among the three groups.Results: While there were no significant differences in the scores of the DHI or NPQ, the total score and anxiety score in HADS in the young group were significantly higher than in the old group (p < 0.05, each). On the other hand, for precipitating conditions, the rate of peripheral vestibular diseases was significantly greater in the old group (77.8%) compared to the young group (41.7.%, p < 0.01).There was no significant difference in the results of caloric testing, vHIT, cVEMPs, or oVEMPs among the three groups. For posturography, the velocity of the center of pressure with eyes-open as well as with eyes-closed was significantly greater in the old group compared to the young group and the middle-age group (p < 0.005, respectively).The clinical characteristics of PPPD were different according to age. Young patients tended to have stronger anxiety than old patients whereas the old patients had a higher proportion of peripheral vestibular diseases among the precipitating conditions compared to young patients.